Effects of injectable extended‐release naltrexone (XR‐NTX) for opioid dependence on residential rehabilitation outcomes and early follow‐up. (4th February 2015) - Leslie, Douglas L.; Milchak, William; Gastfriend, David R.; Herschman, Philip L.; Bixler, Edward O.; Velott, Diana L.; Meyer, Roger E.
Abstract : Background and Objectives: Little is known about the use of extended‐release naltrexone (XR‐NTX) during residential rehabilitation, and its effects on early outcomes and rates of follow‐up treatment. This study examined patient characteristics and rates of treatment completion and engagement in post‐residential care of opioid dependent patients who received XR‐NTX during residential rehabilitation, compared with patients who did not receive this medication. Methods: Electronic records for opioid dependent patients from three Pennsylvania residential detoxification and treatment facilities ( N  = 7, 687) were retrospectively analyzed. We determined the proportion of patients who received XR‐NTX (INJ), and compared rates of treatment completion and engagement in follow‐up care relative to a naturalistic control group of patients recommended for, but not administered, XR‐NTX (Non‐INJ). Data on whether the patient initiated follow‐up care were available from one site ( N  = 3, 724). Results: Overall, 598 (7.8%) patients were recommended for XR‐NTX and of these, 168 (28.1%) received injections. Compared to non‐INJ patients, INJ patients were less likely to leave against medical advice (4.8% vs. 30.2%, p  < .001) and more likely to initiate follow‐up care (37.7% vs. 19.7%, p  < .001). These differences remained significant after controlling for demographic covariates using regression analysis. Conclusions: XR‐NTX was associated with higher rates of residential and early post‐residential care engagement in patients with opioid dependence. Scientific Significance: XR‐NTX may be an effective adjunct in the residential treatment and aftercare of patients with opioid dependence. (Am J Addict 2015;24:265–270)